A82 CORRELATION OF MRE INTERPRETATION USING CONSENSUS RECOMMENDATIONS WITH VIDEO CAPSULE ENDOSCOPY IN PEDIATRIC IBD. (15th March 2019) - Yang, J; Al-Hashmi, G; Walsh, C M; Putra, J; Siddiqui, I; Castro, D; Greer, M
Abstract: Background: Crohn's disease (CD) is a chronic inflammatory disease of the gastrointestinal (GI) tract which involves small bowel in up to 70% of patients. Detecting intestinal disease represents a challenge as it is inaccessible to upper or lower GI endoscopy, instead requiring magnetic resonance enterography (MRE) and/or video capsule endoscopy (VCE). Jejunal assessment on MRE can be limited if suboptimally distended. VCE is capable of visualizing the entire small bowel but limited to the lumen and more invasive. Few studies have specifically evaluated diagnostic accuracy of MRE for jejunal inflammation in pediatric patients. Aims: To determine diagnostic accuracy of MRE compared to VCE for jejunal disease in pediatric patients with suspected or proven CD. Methods: Ethics approval was obtained for this retrospective study. Patients ≤ 18 years who had VCE and MRE within 6 months between 2012–2017 at Sickkids Hospital were included. Exclusion criteria were unavailability of VCE report, nondiagnostic/incomplete MRE and non-visualisation of bowel on VCE, with small bowel divided into 5 segments: esophagus/stomach/duodenum, jejunum, proximal ileum, distal ileum and terminal ileum. Blinded review of MRE was performed by a pediatric radiology fellow using recently published MRE consensus guidelines. Data for VCE was obtained from reports. Segments were defined as normal or abnormal for MRE and VCE, specific abnormalities recorded, with statistical analysis for MRE-VCE agreements calculated. Results: The final cohort was 20 patients (13 female), age range 8–17 years (median 16 years), with a time interval between MRE and VCE of 6–172 days (mean 88.1 days). Eighteen MRE were performed at 1.5 Tesla (T), 2 at 3T. MRE was positive in 6 patients (30%) and 9/91 bowel segments (9.9%); VCE was positive in 18 patients (90%) and 47/91 segments (51.6%). MRE-VCE disagreement was mostly due to superficial lesions in the stomach, duodenum and jejunum, including erythema, small ulcers, erosions and vascular ectasia. In these cases the time interval between MRE and VCE was wider, ranging between 60 to 170 days, likely contributing to a higher disagreement rate and lower MRE sensitivity. Conclusions: MRE has high specificity and PPV for detecting small bowel disease, however low sensitivity for detecting superficial lesions in proximal small bowel. Funding Agencies: Ferring Scholarship Grant Award